Urihi A: A Terra-Floresta Yanomami - Welch, James R. (Ethnobiology Letters, 2010)
Review of Urihi A: A Terra-Floresta Yanomami. Bruce Albert and William Milliken with Gale Goodwin Gomez. São Paulo: Instituto Socioambiental, 2009. 207 pp., illustrations, tables, bibliography, appendices, index. Paperback ISBN: 978‐85 85994‐72‐3.